Story and Structure / Fifht Edition - Perrine Laurence (Harcourt Brace Jovanovich, Publishers, 1978)
Preface, The Elements of the Short Story, Escape and Interpretation, Plot, Character, Theme, Point of View, Symbol and Irony, Emotion and Humor, Fantasy, The Scale of Value, Stories for Further Reading, Glossary of Fictional Terms.
Preface, The Elements of the Short Story, Escape and Interpretation, Plot, Character, Theme, Point of View, Symbol and Irony, Emotion and Humor, Fantasy, The Scale of Value, Stories for Further Reading, Glossary of Fictional Terms.